GEOMORPHOLOGICAL FACTOR DETERMINING STRUCTURAL FEATURES OF THE COMPOSITION OF LATERITIC BAUXITE WEATHERING CRUST FOUTA DJALON-MANDINGO - L K Filatova; Gomes Jalica Correia (RUDN Journal of Engineering Research, 2016)
The article considers the impact of the geomorphological factors on the structural features of the lateritic weathering crusts on the example of the province Fouta Jallon Mandingo.In a given area lateritic (including bauxite) weathering crusts formed mainly by silica-clastic sedimentary rocks (aleuro-pelites and argillites and fine-grained Sandstone) platform cover, deposited sub horizontally everywhere, and dolerites, sills of these deposits. The parent substrate in these areas is close in its composition and occurrence, and climatic conditions are similar.In the study area the relief is generalized in the form presented by the combination of flat, sloping and progesterone the surfaces, represent fragments of aligned surfaces of different ages with different absolute elevations of 100-120 m to 1450-1538 m; from West to East to the axis of the structure increases the number of steps and their absolute marks; the slopes separating the surface - a relatively shallow (10-15°) to steep and steep; flat land of the lower geomorphic levels, that are embedded in the valleys of the rivers and their tributaries; in this case, from West to East from the coastal plains to the axis of the morphological structure of the Fouta Jallon-Mandingo the absolute level of the bottom of geomorphological levels rise from 70-100 m in the West, in the basins Tinguilinta and cogon, and up to 500-700 m in the central part of the Fouta Jallon-Mandingo; the actual bottoms of valleys of the main rivers complex c young late Pleistocene and Holocene terraces, floodplain and channel deposits.